Long-Term prognosis of radiofrequency catheter ablation for atrial fibrillation with different subtypes of heart failure in the era of ablation index guidance - Qiao, Yu; Zhao, Zhen; Cai, Xiang; Guo, Yulong; Fu, Mingpeng; Liu, Ke; Guo, Jinrui; Guo, Tao; Niu, Guodong (Frontiers in Cardiovascular Medicine, 2022)
Background The long-term outcomes of ablation index (AI)-guided radiofrequency catheter ablation (RFCA) on atrial fibrillation (AF) and different subtypes of heart failure (HF) remain unknown. The aim of the study was to evaluate the long-term prognosis of AI-guided RFCA procedures in patients with AF and concomitant HF. Methods We retrospectively included consecutive patients with AF and HF who underwent the initial RFCA procedure with AI guidance from March 2018 to June 2021 in our institution. The patients were categorized into two groups: HF with preserved ejection fraction (HFpEF) group and HF with mid-range ejection fraction (HFmrEF) +HF with reduced ejection fraction (HFrEF) group. Results A total of 101 patients were included. HFpEF and HFmrEF + HFrEF groups consisted of 71 (70.3%) and 30 patients (29.7%), respectively. During a median follow-up of 32.0 (18.2, 37.6) months, no significant difference was detected in AF recurrence between groups (21.1 vs. 33.3%) after multiple procedures, whereas the incidence of the composite endpoint of all-cause death, thromboembolic events, and HF hospitalization was significantly lower in HFpEF group (9.9 vs. 25.0%, Log-rank p = 0.018). In multivariable analysis, a history of hypertension [hazard ratio (HR) 4.667, 95% confidence interval (CI) 1.433–15.203, p = 0.011], left ventricular ejection fraction (LVEF) < 50% (HR 5.390, 95% CI 1.911–15.203, p = 0.001) and recurrent AF after multiple procedures (HR 7.542, 95% CI 2.355–24.148, p = 0.001) were independently associated with the incidence of the composite endpoint. Conclusion Long-term success could be achieved in 75% of patients with AF and concomitant HF after AI-guided RFCA procedures, irrespective of different HF subtypes. Preserved LVEF was associated with a reduction in the composite endpoint compared with impaired LVEF. Patients with recurrent AF tend to have a poorer prognosis.